The Religion of the Etruscans - Simon, Erika; De Grummond, Nancy Thomson (Book collections on Project MUSE., 2006)
Includes information on Aphrodite, Apollo, Apulu, Artumes, Astarte, Athena, Atunis, birds, calendars, children, divination, funerary ritual, Hercules, Jupiter, lightning, Mars, Minerva, Neptune, Odysseus, Persephone, Pliny the Elder, prophecy, Pyrgi, Satyrs, Tages, Tarquinii, temples, thunder, Turan, Uni, Vei, Veii, Vulci, etc.